Arborine, a quinazolin-4-one antimicrobial alkaloid from Glycosmis pentaphylla (Retz.) DC - Md Taib, Nurhaya; Mohd Hassan, Norazian; Mohd Kamal, Laina Zarisa; Soe, May Khin (2010)
Quinazolin-4-one is a type of alkaloid that possesses a chromophore with some structural similarities to that of the pharmacophore of the conventional 4-quinolone antimicrobial agents. Therefore it is presumed that this type of natural quinazoline alkaloid could also share the same activity as the conventional quinolone agents. These characteristics found a great importance in view to find new structural type in overcoming the emergence of quinolone resistance against some microbes which has been a disturbing feature of microbial infections. In this study the leaves of Glycosmis pentaphylla (Retz.) DC., a small tree or shrub from the genus Glycosmis of the Rutaceae family were extracted following acid base extraction method to furnish crude alkaloidal extract. The extract was then fractionated by column chromatography and each fraction was screened by using TLC Agar Overlay Bioautographic Assay for antimicrobial active alkaloids against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922 and Candida albicans ATCC 90028. The active fraction was re-column chromatographed for the isolation of the active alkaloids. This bioassay-guided isolation has afforded arborine or 2-benzyl-1-methylquinazol-4-one as the active principle. Arborine is a simple substituted quinazolin-4-one which is characteristic alkaloid of G. pentaphylla leaves. Quantitative antimicrobial activity was determined by means of the minimum inhibitory concentration (MIC) and the minimum bacteriocidal concentration (MBC) using broth microdilution assay. The MIC value of arborine against the tested microbes ranged between 2000 µg/ml and 500 µg/ml whereas the MBC values against all microbes are above 2000 µg/ml. The results suggested that arborine may provide a new structural type for synthesizing new quinolone agent and also a natural candidate for antimicrobial combination study.